CORRELATION BETWEEN PERSONAL HYGIENE AND INFECTION OF INTESTINAL HELMINTHS AMONG STUDENTS AT THE PUBLIC ELEMENTARY SCHOOL 3 ABELI, KENDARI INDONESIA - Rosanty, Anita (YCAB Publisher & IAKMI SULTRA, 2016)
Backgrounds: Intestinal helminth is one of diseases derived from environment and still becomes a helath problem in Indonesia until today. The high number of intestinal helminth prevalence in Indonesia is related with bad personal hygiene, including handwashing habit, nail hygiene, and foot-wear wearing habit.Objectives: The objective of this research is to know the correlation between the infection of intestinal helminths with handwashing habit, nail hygiene, and foot-wear wearing habit of the students at the Public Elementary School 3 Abeli Kendari Indonesia.Methods: This research was a cross sectional study with an observational analysis. There was 134 respondents were recruited using total sampling.Results: Findings revealed that there were 27 respondents (20.1 %) who had handwashing habit with good category, and 107 respondents (79.9) had handwashing habit with poor category. There were 32 respondents (23.9%) had nail hygiene with poor category, and 102 respondents (76.1 %) had nail hygiene with good category. There were 52 respondents (38.8%) had not good foot-wear wearing habit, and 82 respondents (61.2%) had good foot-wear wearing habit. There was a correlation between handwashing habit, nail hygiene, foot-wear wearing habit and the infection of intestinal helminth among students of public elementary school 3 Abeli Kendari cityConclusion: There were significant relationship between personal hygiene and intestinal helminth. Thus, it is suggested that parents, school teachers, and other significant persons need to maintain the habit of personal hygiene of the students that consists of handwashing habit, nail hygiene, foot-wear wearing habit.